Pengaruh Upah Minimum, PDRB dan Jumlah Industri Terhadap Penyerapan Tenaga Kerja Sektor Industri di Karesidenan Madiun pada Tahun 2017-2020 - Amin Widyaningrum; Selfia Bintariningtyas (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
The purpose of this research is to determine the effect of the Minimum Wage, PDRB, and the Amount of Industry on the Absorption of Manpower in the Industrial Sector in the Madiun Residency in 2017-2020. This study uses quantitative research through secondary data from related agencies, namely the Central Statistics Agency (BPS) of East Java Province. While the analytical method used is panel data regression analysis. Based on the results of the study, it shows that the minimum wage variable has a significant negative effect on the employment in the industrial sector in the Madiun Residency, PDRB has a significant positive effect on the employment in the industrial sector in the Madiun Residency and the Amount of Industry has a positive and insignificant effect on employment in the industrial sector in the Madiun Residency.